Evaluating the fodder and Quality of Two Different Rangelands in Sulaimani Governorate, Kurdistan, Iraq - Tara Omar Mohammed; Jwan Gharib Rafaat (Kufa Journal for Agricultural Sciences)
This study was conducted during 2015 in Sulaimani governorate at two main different locations of Sharazoor and Penjwen, each with some sub-locations, to estimate fresh yield, dry yield, dry matter and animal unit. The rangeland areas of Sulaimani governorate located between 35° 10' - 36° 27' N and 44° 40' - 46° 22' E were restricted 126546.00, and 29542.00 ha for Sharazoor, and Penjwen locations, respectively. The most important results indicated that, Sharazoor location gave the maximum value of total dry yield 41380.50 ton and 125395.40 Animal unit/three months, while Penjwen location which gave the minimum value total dry yield of 25544.1 ton and77406.30 animal unit/three months. The highest fresh and dry yield were obtained bySharazoor location which were 19563.36 and 3224.04 kg/ha, respectively, in which Penjwen location gave the minimum value of 11872.80 kg/ha and 2369.81 kg/ha for fresh yield and dry yield, respectively. Results of chemical analysis for the grass and legume plants showed that there were differences between locations. Sharazoor location gave the maximum percentage of protein content, fiber, phosphorus and potassium which were (11.81, 20.5, 1.45, and 1.02 %) respectively, for legume plants, However, chemical contents for grass plant showed that Penjwen location gave the maximum percentage of protein, carbohydrate, fiber, magnesium and calcium contents which were (9.80, 36.45, 31.50, 0.18, 0.22%), respectively. The mean of protein, oil, K, Mg, Ca and ash in legume plant were (1.56, 1.50, 1.07, 1.52, 2.25and1.16) times higher than their concentration in the grass respectively. But the value of carbohydrate and fiber in the grass were (1.73 and 1.21) times higher than their concentration in the legumes respectively. The concentration of phosphorus is equal in both types of plants and it is more than normal concentration